Penerapan Terapi Murotal Al-Qur’an Surah Ar-Rahman Pada Tekanan Darah Klien Dengan Hipertensi - Urmila Puspita Arum; Ida Nur Imamah (Jurnal Siti Rufaidah, 2024)
Background: Hypertension is a condition where systolic blood pressure exceeds 140 mmHg and/or diastolic pressure exceeds 90 mmHg. One non-pharmacological method to reduce blood pressure is the recitation of Quranic verses. Method: The method used in this research is quantitative, employing a case study approach by comparing pretest and posttest results. Objective: This study aims to describe the effectiveness of murottal therapy in reducing blood pressure in clients with hypertension. Results: The application of Al-Qur'an Surah Ar-Rahman murottal therapy for 11 minutes at a volume of 41-60 dB on two respondents showed a decrease in blood pressure from 161/94 mmHg and 164/100 mmHg to 140/85 mmHg and 145/90 mmHg, respectively. This study discusses an intervention focused on auditory therapy. Conclusion: There is a reduction in blood pressure following the application of Al-Qur’an Surah Ar-Rahman murottal therapy.